2012
DOI: 10.1007/s12010-011-9511-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Concentration on Dark Fermentation Hydrogen Production Using an Anaerobic Fluidized Bed Reactor

Abstract: The effect of substrate (glucose) concentration on the stability and yield of a continuous fermentative process that produces hydrogen was studied. Four anaerobic fluidized bed reactors (AFBRs) were operated with a hydraulic retention time (HRT) from 1 to 8 h and an influent glucose concentration from 2 to 25 g L(-1). The reactors were inoculated with thermally pre-treated anaerobic sludge and operated at a temperature of 30 °C with an influent pH around 5.5 and an effluent pH of about 3.5. The AFBRs with a HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 33 publications
1
19
1
11
Order By: Relevance
“…After it had been collected, the cassava wastewater was stored at 5 °C before usage. We chose to use the cassava wastewater with COD of 4 g COD/L, because, according to Amorim et al (2012), this concentration might favor the production of acetic acid and butyric acid (route that favors hydrogen production), whereas higher substrate concentrations would favor the production of solvents. Furthermore, Cappelletti et al (2011) concluded that a lower cassava wastewater COD produces a large amount of hydrogen.…”
Section: Inoculum and Fermentation Mediummentioning
confidence: 99%
“…After it had been collected, the cassava wastewater was stored at 5 °C before usage. We chose to use the cassava wastewater with COD of 4 g COD/L, because, according to Amorim et al (2012), this concentration might favor the production of acetic acid and butyric acid (route that favors hydrogen production), whereas higher substrate concentrations would favor the production of solvents. Furthermore, Cappelletti et al (2011) concluded that a lower cassava wastewater COD produces a large amount of hydrogen.…”
Section: Inoculum and Fermentation Mediummentioning
confidence: 99%
“…However, the abundance of EtOH production from the mixed culture used was most likely due to the dominance of Enterobacter and/or Klebsiella, as EtOH is one of the major products of these facultative anaerobes [13,30].…”
mentioning
confidence: 99%
“…1). Hydrogen volume achievements in suitable condition were not as high as many earlier reports [2,3,13,14,16]. Since the hydrogen yield of strain Trau DAt in suitable condition was not high in comparison to some other thermophilic strains, the response surface methodology (RSM) with central composite design was applied for three important factors including glucose, yeast extract, iron concentration to enhance hydrogen production yield.…”
Section: Biohydrogen Production By Dark Fermentation Under Suitable Cmentioning
confidence: 97%
“…On the other hand, fermentative bacteria represent a promising means not only to reclaim energy from wastes in the form of hydrogen but also to utilize the wastes as sources. In addition, the dark fermentation using fermentative bacteria has many advantages: (1) It can produce H 2 all day long without light; (2) A variety of carbon sources can be used as substrates even biomass; (3) It produces valuable metabolites such as butyric, lactic and acetic acids as by products; (4) It is anaerobic process, so there is no O 2 . Thus, the dark fermentation for hydrogen production is the best choice for commercial biohydrogen production [1,4,5,9,12,14,20,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation